Rare Primary Adrenal Tumor: A Case Report of Teratomas and Literatures Review - Wang, Xiaomin; Li, Xiaoguang; Cai, Hongjia; Xiao, Wei; Su, Peng; Huang, Xiang; Luo, Xu; Zhang, Neng; Fu, Ni (Frontiers in Oncology, 2022)
Teratomas are very rare, originating from embryonal germ layers. The majority of them are mature, most common in the gonads, and with only 15% out of gonads. In particular, primary adrenal teratomas are extremely rare. The present study reported a case of a young female patient with right adrenal tumor who underwent intermittent pain in the right waist and abdomen and whose CT of adrenal gland showed an 88 mm × 79 mm × 69 mm mass. Besides, her adrenal gland-related hormones are not abnormal. Laparoscopic adrenal tumor resection was performed on her and the histopathological results confirmed that the mass was mature adrenal teratomas. As a newly diagnosed case, strict and regular follow-up is needed, and it is also necessary to detect her AFP and check her adrenal CT in the future. In addition, we have reviewed the literature from 1952 to the present, and a total of 49 cases of adrenal teratoma have been identified and analyzed.